Variability in the implementation of voicing in American English obstruents. (January 2016) - Davidson, Lisa
Abstract: Previous research has shown that in languages like English, the implementation of voicing in voiced obstruents is affected by linguistic factors such as utterance position, stress, and the adjacent sound. The goal of the current study is to extend previous findings in two ways: (1) investigate the production of voicing in connected read speech instead of in isolation/carrier sentences, and (2) understand the implementation of partial voicing by examining where in the constriction voicing appears or dies out. The current study examines the voicing of stops and fricatives in the connected read speech of 37 speakers. Results confirm that phrase position, word position, lexical stress, and the manner and voicing of the adjacent sound condition the prevalence of voicing, but they have different effects on stops and fricatives. The analysis of where voicing is realized in the constriction interval shows that bleed from a preceding sonorant is common, but voicing beginning partway through the constriction interval (i.e., negative voice onset time) is much rarer. The acoustic, articulatory, and aerodynamic sources of the patterns of phonation found in connected speech are discussed. Highlights: Voicing in American English obstruents in connected speech is investigated. Stops are most often devoiced word initially and adjacent to obstruents. Fricatives are less voiced word finally and less affected by adjacent sounds. Voicing often bleeds from preceding sound, but starting in stop closure is rare. English is a good test case for examining phonetic naturalness of voicing.